Relasi Kuasa dan Tantangan Kekerasan Terhadap Perempuan di Perguruan Tinggi Islam - Asy'ari (Palita: Journal of Social Religion Research, 2022)
This paper will review about sexual violence against women that occurred in Islamic universities by using Michael Foucault's power relations analysis. The violence referred to in this paper refers to Johan Galtung's violence which divides violence into three, namely direct violence, structural violence and cultural violence. The method used in this paper is a literature review research. The results of this study, of the many cases of sexual violence in Islamic universities, are only like the top of the pyramid triangle, while the large goiter at the bottom of the pyramid is a challenge to be uncovered and resolved. This is because it is related to power, structure and cultural relations which often not only obscure but also reverse the actual phenomenon